IMPLEMENTASI MODEL PROBLEM BASED LEARNING UNTUK PENINGKATAN PRESTASI BELAJAR PESERTA DIDIK SMA PADA MATERI ANCAMAN TERHADAP IDEOLOGI PANCASILA DI ERA DIGITAL - Sinaga, Johannes Leonard; Damanik, Prince Clinton Immanuel Christian (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2025)
This research followed the classroom action research design by Kemmis McTaggart and was conducted in three cycles, each consisting of planning, implementation, observation, and reflection stages. A total of 30 Grade XI students were the subjects of this study. Data were collected using learning achievement tests and observation. Quantitative descriptive analysis was applied to the learning achievement data, and qualitative analysis was used for the observation data. The research findings indicate a significant and continuous improvement in student learning achievement. The class average score increased from 59.83 in Cycle I, to 75.00 in Cycle II, and then to 93.17 in Cycle III. The classical completeness level also showed a substantial improvement, from 26.67% in Cycle I, to 63.33% in Cycle II, reaching 100.00% in Cycle III, thereby surpassing the 70% target. The PBL model proved effective in assisting students to comprehend complex and relevant material related to current issues, as well as enhancing their active participation. This research is expected to contribute to the development of more innovative and responsive Pancasila and Civics Education (PPKn) learning strategies for the challenges in the digital era.